Given:

**a=b**. Applying some basic identity transformations, we get:

a=b
a^2-ab=a^2-b^2
a(a-b)=(a+b)(a-b)
a=a+b
a=a+a
a=2a
1=2

With such a proof, we can show that
1=2, pi=E, 10000000000000=1, etc.... Can you spot the flaw?

Given: a=b. Applying some basic identity transformations, we get:

a=b --------(Step 1)

a^2-ab=a^2-b^2 --------(Step 2)

a(a-b)=(a+b)(a-b) --------(Step 3)

a=a+b --------(Step 4)

a=a+a --------(Step 5)

a=2a --------(Step 6)

1=2 --------(Step 7)

Given a = b implies (a - b) = 0, and as we know that anything divided by zero is undefined, thus the flaw lies in the fourth step which we have obtined from step 3 on division by (a - b), that is, on division by zero, which cannot be done.

That's it.